2018
DOI: 10.1080/17512433.2018.1425614
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine dose-response effect on postoperative cognitive deficit: meta-analysis and meta-regression

Abstract: The true influence of the perioperative intravenous lidocaine on the development of postoperative cognitive deficit (POCD) in coronary artery bypass grafting (CABG) remains controversial. The principal aim is to undertake a meta-regression to determine whether moderator variables mediate the relationship between lidocaine and POCD. Areas covered: We searched the Web of Science, PubMed database, Scopus and the Cochrane Library database (up to June 2017) and systematically reviewed a list of retrieved articles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
12
1
Order By: Relevance
“…Nevertheless, a lack of validation regarding the strength of evidence because TSA was not performed as well as the small number of patients in those meta-analyses remain important concerns. [ 21 , 22 ] Our findings from TSA showed that the prophylactic effect of intravenous lidocaine on cognitive dysfunction remained inconclusive at an early postoperative period. Furthermore, the association became nonsignificant when 1 study reporting a circulating lidocaine concentration up to 4.78 to 7.1 μg/mL [ 20 ] was removed.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, a lack of validation regarding the strength of evidence because TSA was not performed as well as the small number of patients in those meta-analyses remain important concerns. [ 21 , 22 ] Our findings from TSA showed that the prophylactic effect of intravenous lidocaine on cognitive dysfunction remained inconclusive at an early postoperative period. Furthermore, the association became nonsignificant when 1 study reporting a circulating lidocaine concentration up to 4.78 to 7.1 μg/mL [ 20 ] was removed.…”
Section: Discussionmentioning
confidence: 92%
“…Two previous meta-analyses [ 21 , 22 ] focused on 5 RCTs had suggested a correlation between the use of intravenous lidocaine and a reduced risk of cognitive deficit at about postoperative 2 weeks, but not at 8 to 10 weeks. Nevertheless, a lack of validation regarding the strength of evidence because TSA was not performed as well as the small number of patients in those meta-analyses remain important concerns.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lignocaine was shown to increase susceptibility to POCD in diabetic patients [ 55 ]. Furthermore, in a meta-analysis involving 688 patients, lignocaine was administered as an infusion from the beginning of the anaesthetic induction to the next 48 h. Results revealed that higher concentrations of lignocaine were associated with more substantial neuroprotective effects [ 5 ].…”
Section: Neuroprotection Interventionsmentioning
confidence: 99%
“…The duration of CPB during cardiac surgery has been associated with a variety of adverse outcomes. Longer CPB times are a recognised risk factor for neurological sequelae following cardiac surgery; however, in a meta-analysis by Habibi et al, the use of lignocaine infusions combined with longer CPB times was associated with more favourable neurological outcomes [ 5 ]. Perfusion flow generated by CPB is usually non-pulsatile, which contrasts with the physiological pulsatile flow.…”
Section: Neuroprotection Interventionsmentioning
confidence: 99%
“…Results of a meta-analysis showed that a higher concentration of lidocaine can be an effective neuroprotective agent on patients following heart surgery (Habibi et al, 2018). However, there is an ongoing debate in the literature on the effect of lidocaine on cognitive function in noncardiac surgery (Chen et al, 2015;Peng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%